2021
DOI: 10.1080/19420862.2021.1890411
|View full text |Cite
|
Sign up to set email alerts
|

TNB-486 induces potent tumor cell cytotoxicity coupled with low cytokine release in preclinical models of B-NHL

Abstract: The therapeutic potential of targeting CD19 in B cell malignancies has garnered attention in the past decade, resulting in the introduction of novel immunotherapy agents. Encouraging clinical data have been reported for T cell-based targeting agents, such as anti-CD19/CD3 bispecific T-cell engager blinatumomab and chimeric antigen receptor (CAR)-T therapies, for acute lymphoblastic leukemia and B cell non-Hodgkin lymphoma (B-NHL). However, clinical use of both blinatumomab and CAR-T therapies has been limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Using genetically engineered transgenic rats (UniRat and OmniFlic) that express fully human IgG antibodies together with an NGS-based antibody discovery pipeline (TeneoSeek), [25][26][27][28] we have developed TNB-585. Methods for generating antibodies targeting CD3 in OmniFlic animals have been previously described.…”
Section: Materials and Methods Immunization Ngs Clonotype Analysis And Cloningmentioning
confidence: 99%
“…Using genetically engineered transgenic rats (UniRat and OmniFlic) that express fully human IgG antibodies together with an NGS-based antibody discovery pipeline (TeneoSeek), [25][26][27][28] we have developed TNB-585. Methods for generating antibodies targeting CD3 in OmniFlic animals have been previously described.…”
Section: Materials and Methods Immunization Ngs Clonotype Analysis And Cloningmentioning
confidence: 99%
“…To examine the specific binding of the selected scFv-Fc and IgG1 antibodies to the EphA2 receptor on the surface of tumor cells, flow cytometry was performed as previously described [ 56 , 57 ]. The purified bivalent recombinant antibody, scFv-Fc; and full-length antibody, IgG1, were added to PC-3 and A549 cells (2 × 10 5 in 1 × PBS) as primary antibodies with final concentrations set at 1.25 μg/mL, 5 μg/mL, and 20 μg/mL for an incubation at 4°C for 1 h. The final concentration in the blank group was 1.25 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The molecule is constituted of a high-affinity anti-CD19 heavy chain and a low-affinity anti-CD3 light chain, the latter with low-activating potential. In vitro models have demonstrated that the cytokine secretion (i.e., IL-2, IFN-γ, IL-6, IL-10, and TNF) by CD3 + cells is minimal even at saturating doses for tumor lysis ( 34 , 35 ). A phase 1 study (NCT04594642) is currently testing TNB-486 for R/R B-cell non-Hodgkin lymphoma in patients who have received 2 or more prior lines of therapy.…”
Section: Bispecific T Cell Engagersmentioning
confidence: 99%